The Spillover Effect of Antitrust Enforcement - Block, Michael K.; Feinstein, Jonathan S. (The Review of Economics and Statistics, 1986)
We address the question of how the threat of antitrust enforcement spills over from one industrial submarket to another. We build a formal model describing the technology through which an initial antitrust indictment can reveal evidence of additional infractions in the same industry. Our approach is organized around the belief that the flow of information on antitrust violations is closely linked to commodity flows. As it turns out, our method proves able to explain the differential response of highway construction cartels in various states to recent changes in the severity of antitrust sanctions.